Tolkien among the moderns - Wood, Ralph C. (University of Notre Dame Press, 2015)
"It has long been recognized that J. R. R. Tolkien's work is animated by a profound moral and religious vision. It is less clear that Tolkien's vision confronts the leading philosophical and literary concerns addressed by modern writers and thinkers. This book seeks to resolve such uncertainty. It places modern writers and modern quandaries in lively engagement with the broad range of Tolkien's work, while giving special attention to the textual particularities of his masterpiece, The Lord of the Rings. In ways at once provocative and original, the contributors deal with major modern artists and philosophers, including Miguel de Cervantes, Friedrich Nietzsche, Emmanuel Levinas, Iris Murdoch, and James Joyce. The essays in Tolkien among the Moderns also point forward to postmodernism by examining its implications for Tolkien's work. Looking backward, they show how Tolkien addresses two ancient questions: the problems of fate and freedom in a seemingly random universe, as well as Plato's objection that art can neither depict truth nor underwrite morality. The volume is premised on the firm conviction that Tolkien is not a writer who will be soon surpassed and forgotten--exactly because he has a permanent dwelling place "among the moderns." "This collection of essays places Tolkien in the context of the big themes of philosophy, historically and today. It will speak to readers who are already drawn to the work of Tolkien and who either have a desire to see into his work more deeply or desire to see how his work might be employed to think about other matters, for example, how might the work of Tolkien impact the so-called warfare between poetry and philosophy. I believe that the work of Tolkien is here to stay, that it will continue to stand the test of time, and that intelligent, curious readers will find Tolkien among the Moderns deeply rewarding." --Charles Taliaferro, St. Olaf College "--